UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP BAKTERI PEMBUSUK IKAN SEGAR (PSEUDOONAS AERUGINOSA) - Widowati, Imas; Efiyati, Siti; Wahyuningtyas, Sari (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The objective of the research is to find out whether the extract of kelor (Moringa oleifera) leaves can be used as antibacteria of decomposer bacteria (Pseudomonas aeruginosa) in fresh fish and to find out the most effective concentration of kelor extract as antibacteria. The research starts with making the extract of kelor (Moringa oleifera) leaves by using maceration technique. The next step is making Natrium Agar (NA) as the medium for growing the bacteria and the third step is testing the extract of kelor (Moringa oleifera) leaves on the bacteria (Pseudomonas aeruginosa) by using the aseptic technique and streak plate method. The bacteria were incubated for approximately 24 hours in the room temperature. Next, the diameter of the clearzone produced in each treatment is measured. In this research there are five variations of kelor leaf extract concentrations, namely 0%, 25 %, 50%, 75%, and 100% with five repetitions. Based on the SPSS analysis using Anava testing, the significance level is 0.007 â‰¥ 0.005. It shows those five treatments of giving the extract of kelor leaves with the concentrations of 0%, 25%, 50%, 75%, and 100% do not significantly affectthe activities of Pseudomonas aeruginosa bacteria. Based on the result of the observation, the average length of the diameter of clear zone on the extract concentration of 50% is the biggest, which is 1 mm long. Thus, it can be concluded that the extract of kelor (Moringa oleifera) leaves can be used as antibacteria for the decomposer (Pseudomonas aeruginosa) bacteria of fresh fish.